The developmental miR-17-92 cluster and the Sfmbt2 miRNA cluster cannot rescue the abnormal embryonic development generated using obstructive epididymal environment-producing sperm in C57BL/6 J mice - Xunwei Wu; Xiaomei He; Qian Liu; Honggang Li (BMC, 2022)
Abstract Background Sperm, during epididymal transit, acquires microRNAs(miRNAs), which are crucial for embryonic development. However, whether sperm miRNAs influenced by an obstructive epididymal environment affect embryonic development remains unknown. Method The sham operation and vasectomy were performed in C57BL/6 J mice to create the control group (CON) and the obstructive epididymal environment group(OEE) group, respectively. The morphology of the testis and epididymis was observed using hematoxylin and eosin staining (HE staining) to establish the OEE mice model. The sperm quality test, intracytoplasmic sperm injection (ICSI), and epididymosomes fusion were employed to observe the effect of the obstructive epididymal environment on sperm and resultant embryonic development. The alteration of the sperm small RNA (sRNA) profile was analyzed by sRNA sequencing. RT-qPCR and DNA methylation were applied to observe the effect of obstructive epididymis on the expression of sperm miRNAs. The miRNAs microinjection was used to explore the impacts of sperm miRNAs on embryonic development. Results We confirmed postoperative 8-week mice as the OEE mice model by examining the morphology of the testis and epididymis. In the OEE group, we observed that sperm quality degraded and the development potential of embryos was reduced, which can be saved by the normal epididymal environment. The sperm sRNA sequencing revealed that the expression of the developmental miR-17-92 cluster and the Sfmbt2 miRNA cluster was downregulated in the OEE group. The expression of these two miRNA clusters in epididymis was also downregulated and regulated by DNA methylation. However, the downregulation of either the miR-17-92 cluster or the Sfmbt2 miRNA cluster in normal zygotes did not impair embryonic development. Conclusion The obstructive epididymal environment influences sperm quality and resultant embryonic development, as well as the abundance of the developmental miR-17-92 cluster and the Sfmbt2 miRNA cluster in sperm, but these miRNA clusters are not the cause of abnormal embryonic development. It implies that epididymis is important in early embryonic development and may play a potential role in sperm epigenome.